Pulse Dosing of Antibiotic Enhances Killing of a Staphylococcus aureus Biofilm - Meyer, Kirsten J.; Taylor, Hannah B.; Seidel, Jazlyn; Gates, Michael F.; Lewis, Kim (Frontiers in Microbiology, 2020)
Biofilms are highly tolerant to antibiotics and underlie the recalcitrance of many chronic infections. We demonstrate that mature Staphylococcus aureus biofilms can be substantially sensitized to treatment by pulse dosing of an antibiotic – in this case oxacillin. Pulse (periodic) dosing was compared to continuous application of antibiotic and studied in a novel in vitro flow system which allowed for robust biofilm growth and tractable pharmacokinetics of dosing regimens. Our results highlight that a subpopulation of the biofilm survives antibiotic without becoming resistant, a population we refer to as persister bacteria. When oxacillin was continuously present the persister level did not decline, but, importantly, providing correctly timed periodic breaks decreased the surviving population. We found that the length of the periodic break impacted efficacy, and there was an optimal length that sensitized the biofilm to repeat treatment without allowing resistance expansion. Periodic dosing provides a potential simple solution to a complicated problem.